Post operative pancreatic fistula associated with failure to rescue on pancreatic cancer undergoing pancreatic resection: a single centre experience - Ida Bagus, Budhi; Bagus, Metria Ida; Soewoto, Widyanti; Hanis Setyono; Wibisono; Yarso, Kristanto Yuli (International Surgery Journal, 2024)
Pancreatic resection was known as the gold standard treatment for resectable pancreatic cancer. Post operative pancreatic fistula was common following pancreatic resection for tumor of the pancreas (head, body or tail of the pancreas). According to the Clavien-Dindo classification, the presence of the pancreatic fistula after resection was associated with increased rate of morbidity and mortality for the patients. We would evaluate cases of resectable pancreatic cancer (head and tail of the pancreas) undergoing open pancreatic resection in our centre (low volume centre). Post operative pancreatic fistula were evaluated by abdominal CT scanning and increased amylase level from intra peritoneal drain. The patients whose cannot survive after pancreatic resection were classified as failure to rescue. The presence of cardio-pulmonary morbidity was excluded from this study. Six cases were recorded in this study, 4 cases were head pancreatic cancer and 2 cases was tail pancreatic cancer. The histopathology results were acinar cell pancreatic cancer. Post operative pancreatic fistula was found on 1 case of head pancreatic cancer, classified as Clavien-Dindo grade IV, relaparotomy was done. This patient had sepsis associated post operative pancreatic fistula and can not survive during evaluation (on 14th post operative days). For the rest of the patients, there were no pancreatic fistula and had good outcome with no post operative morbidity. The presence of uncontrolled post operative pancreatic fistula was associated with failure to rescue on pancreatic cancer undergoing resection.